Search for ways to improve competitive success at XXIII (2018) Winter Olympics in PyeongChang (Korea) - Golovachev, A. I.; Kolykhmatov, V. I.; Shirokova, S. V. (Theory and Practice of Physical Culture, 2017)
Abstract: The article considers the elite racing skiers` pre-season training process prior to the XXIII (2018) Winter Olympics in PyeongChang (Republic of Korea) and the potential for the process being customized to the individual chronobiological, climatic and geographical aspects of the places of the final pre-season training. The study offers schedules for the peak functionality of the elite racing skiers being attained by the time of the FIS competitions in PyeongChang (Republic of Korea) at the place and in the period of the XXIII (2018) Winter Olympics. The study was designed based on a comparative analysis of the functionality variations in the athletes of two groups engaged in the final training stage; the training being designed as required by the two-stage (Group I, Intensive Training Stage [ITS] at middle altitudes of the Amut Mountain in the Khabarovsk Territory) and one-stage (Group II, ITS in PyeongChang at 780 m altitude) models of PyeongChang-customized trainings.